2015
DOI: 10.3233/jad-142304
|View full text |Cite
|
Sign up to set email alerts
|

Partial Loss of the Glutamate Transporter GLT-1 Alters Brain Akt and Insulin Signaling in a Mouse Model of Alzheimer's Disease

Abstract: The glutamate transporter GLT-1 (also called EAAT2 in humans) plays a critical role in regulating extracellular glutamate levels in the central nervous system (CNS). In Alzheimer’s disease (AD),EAAT2 loss is associated with neuropathology and cognitive impairment. In keeping with this, we have reported that partial GLT-1 loss (GLT-1+/−) causes early-occurring cognitive deficits in mice harboring familial AD AβPPswe/PS1ΔE9 mutations. GLT-1 plays important roles in several molecular pathways that regulate brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 76 publications
(115 reference statements)
1
13
0
1
Order By: Relevance
“…Recently, a study revealed that GLT‐1 loss also caused an apparent compensatory increase in insulin‐degrading enzyme activity in the liver, an organ that has been shown to regulate peripheral aβ levels and expresses GLT‐1, suggesting that partial GLT‐1 loss can cause insulin/Akt (protein kinase B) signaling abnormalities observed in AD (Meeker et al . ).…”
Section: Glutamate Excitotoxicity and Pathologiesmentioning
confidence: 97%
“…Recently, a study revealed that GLT‐1 loss also caused an apparent compensatory increase in insulin‐degrading enzyme activity in the liver, an organ that has been shown to regulate peripheral aβ levels and expresses GLT‐1, suggesting that partial GLT‐1 loss can cause insulin/Akt (protein kinase B) signaling abnormalities observed in AD (Meeker et al . ).…”
Section: Glutamate Excitotoxicity and Pathologiesmentioning
confidence: 97%
“…But how TSG exactly exerts neuronal protective effects remains obscure. It is well known that the injury of neurons in CNS disorders, such as Alzheimer's disease and brain ischemia, can be mediated by the impairment of astrocytic glutamate transporters [18,19]. In brain ischemia, the impairment astrocytic glutamate transporters would induce the over-accumulation of extracellular glutamate and then lead to the over-activation of glutamate receptors [20].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an increase in glutamate concentration at the synaptic cleft triggering excitotoxicity mediated neurodegeneration [ 80 , 82 ]. Nonetheless, loss of EAAT2 function increases the activity of insulin-degrading enzymes in the liver, suggesting that the loss of EAATs causes insulin/protein kinase B signaling abnormalities in AD [ 83 ]. These findings suggest that EAAT2 loss/dysfunction associated with AD pathology and EAAT2 could be used as a therapeutic target for neuroprotection in glutamate-mediated excitotoxicity.…”
Section: Glutamatergic Systemmentioning
confidence: 99%